Transcription factor 4 expression and correlation with tumor progression in gallbladder cancer - Neogi, Kaushik; Tewari, Mallika; Singh, Ashish Kumar; Sharma, Kavyanjali; Tej, Gullanki Naga Venkata Charan; Verma, Sumit Singh; Gupta, Subash Chandra; Nayak, Prasanta Kumar (Wolters Kluwer Medknow Publications, 2022)
Dysregulation in Wnt/β-catenin signaling has been associated with the initiation and metastasis of cancer cells. Transcription factor 4 (TCF4) (also named as transcription factor 7-like 2) is a key transcriptional factor of the Wnt signaling pathway, which, when interact with β-catenin activates Wnt genes which plays an essential role in tumor development. The expression pattern and clinical significance of TCF4 in gallbladder cancer (GBC) are not yet established. Aims: This study was performed to assess the expression pattern of TCF4 in GBC tissue and attempted to correlate its expression with different clinicopathological parameters. Materials and Methods: The study was conducted on 33 surgically resected specimens of gallbladder carcinoma (GBC) and 12 cases of chronic cholecystitis (CC) as control, which had been confirmed from histology. The expression of TCF4 was performed by the reverse transcription polymerase chain reaction and immunohistochemistry. Results: Relative mRNA expression levels of β-catenin and TCF4 in GBC tissues were significantly (P < 0.05) higher than in CC samples. TCF4 protein expression was observed in 81.82% (27/33) GBC cases. Specifically, among GBC samples, 21.21% (7/33) was graded as strongly positive, 60.61% (20/33) graded as moderately positive, whereas 18.18% (6/33) graded as negative. All 12 CC samples graded as negative. Overall, TCF4 expression in GBC tissues was statistically significant over CC samples (P < 0.05). Moreover, we observed that TCF4 expression was significantly higher (P < 0.05) in high tumor grades than low grade, higher (P < 0.05) in Stage 2 and Stage 3 than Stage 1. Conclusion: The present study suggests that TCF4 may exert an oncogenic role in the progression of GBC and may serve as a new potential candidate biomarker for tumor progression, and it might be a potential therapeutic target against GBC.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: Clinical significance; expression; gallbladder cancer; transcription factor 4; Wnt/β-catenin signaling; β-catenin; beta Catenin; Cell Line; Tumor; Cholecystitis; Gallbladder Neoplasms; Humans; Transcription Factor 4; Transcription Factors; Wnt Signaling Pathway; beta catenin; messenger RNA; transcription factor 4; beta catenin; transcription factor; transcription factor 4; abdominal pain; adult; Article; biliary tract surgery; bloating; cancer growth; cancer surgery; cancer tissue; carcinogenesis; cholecystectomy; chronic cholecystitis; clinical article; clinical feature; computer assisted tomography; controlled study; correlation analysis; dyspepsia; echography; female; gallbladder carcinoma; gallbladder tissue; gallstone; gastrointestinal infection; histology; human; human cell; human tissue; immunohistochemistry; indigestion; jaundice; loss of appetite; male; middle aged; molecular pathology; mRNA expression level; reverse transcription polymerase chain reaction; RNA isolation; cholecystitis; gallbladder tumor; genetics; metabolism; pathology; tumor cell line; Wnt signaling